In search of a surrogate for touch: The effect of haptic imagery on perceived ownership - Peck, Joann; Barger, Victor A.; Webb, Andrea (Journal of Consumer Psychology, 2013)
AbstractPrevious research has shown that individuals value objects more highly if they own them, a finding commonly known as the endowment effect. In fact, simply touching an object can create a perception of ownership that produces the endowment effect. In this paper, we extend this line of research in several ways. First, we show that haptic imagery, or imagining touching an object, can have the same effect on perceived ownership as physical touch. We then demonstrate that haptic imagery can lead to perceptions of physical control, which in turn increase feelings of ownership. Moreover, the more vivid the haptic imagery, the greater the perception of control and the feeling of ownership. Implications for theory and practice are discussed.